2012
DOI: 10.1097/brs.0b013e31823da22d
|View full text |Cite
|
Sign up to set email alerts
|

Patient Comorbidities and Complications After Spinal Surgery

Abstract: Both minor and major complications were found to increase the cost of care in a prospective assessment of spine surgery complications. Specific patient comorbidities and perioperative complications are associated with significant increases in the total cost of care to society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(59 citation statements)
references
References 24 publications
1
54
1
3
Order By: Relevance
“…This suggests that the location of the infection may have little impact on the cost. In a 2012 study evaluating the short-term direct hospital costs of spinal complications, Whitmore et al 32 found a cost increase of $4067 for 30 days after a deep wound infection. The difference between their findings and the $12,619 increase found in our study is likely due to the longer follow-up time of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the location of the infection may have little impact on the cost. In a 2012 study evaluating the short-term direct hospital costs of spinal complications, Whitmore et al 32 found a cost increase of $4067 for 30 days after a deep wound infection. The difference between their findings and the $12,619 increase found in our study is likely due to the longer follow-up time of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical importance of minor adverse events is controversial [14], the economic burden should be considered. While minor adverse events are less costly individually, they appear with high frequency, thus contributing to more than half of the total costs of adverse events [18,44]. Furthermore, these events are the most potentially preventable [18], further enhancing the rationale for addressing them.…”
Section: Discussionmentioning
confidence: 99%
“…In neurosurgery a simple wound infection may lead to multiple reoperations and long antibiotic treatments, and hence cause greater costs than infections in other surgical specialties. 15,25 The use of a surgical checklist is simple and inexpensive, and could indirectly save money, 18 redundant work, and suffer ing of patients. There is a need for surgical checklists in all types of surgery, 13 but especially in neurosurgery.…”
Section: Discussionmentioning
confidence: 99%